2021
DOI: 10.51253/pafmj.v71i3.2692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age, Gender and Duration of Diabetes Mellitus on Thyroid Dysfunction in Patients of Diabetic

Abstract: Objective: To compare the effect of age, gender and duration of diabetes mellitus on thyroid dysfunction in patients of diabetic Study Design: Comparative cross sectional study. Place and Duration of Study: Medicine department, Combined Military Hospital, Peshawar, from Oct 2015 to Oct 2017. Methodology: The study was conducted after taking permission from hospital ethical review committee. Information was entered in the proforma, which included demographic information like age in years, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The meta-analysis included 38 studies that revealed the prevalence and contributing factors of TD among T2DM patients. Among all the papers, 6 of them were from Africa [ 3 , 31 , 35 , 43 , 45 , 51 ], 28 were from Asia [ 3 , 7 – 9 , 11 , 14 , 16 , 23 , 24 , 29 , 32 34 , 37 42 , 44 , 46 , 47 , 49 , 50 , 52 – 58 ], 1 was from Australia [ 48 ], 2 were from Europe [ 10 , 30 ], and 1 was from South America [ 22 ]. Regarding the study design, 9 were case–control, 1 case series, 3 were cohort, 21 were cross-sectional, 1 prospective, and 3 retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis included 38 studies that revealed the prevalence and contributing factors of TD among T2DM patients. Among all the papers, 6 of them were from Africa [ 3 , 31 , 35 , 43 , 45 , 51 ], 28 were from Asia [ 3 , 7 – 9 , 11 , 14 , 16 , 23 , 24 , 29 , 32 34 , 37 42 , 44 , 46 , 47 , 49 , 50 , 52 – 58 ], 1 was from Australia [ 48 ], 2 were from Europe [ 10 , 30 ], and 1 was from South America [ 22 ]. Regarding the study design, 9 were case–control, 1 case series, 3 were cohort, 21 were cross-sectional, 1 prospective, and 3 retrospective studies.…”
Section: Resultsmentioning
confidence: 99%